Religious Humanism Synergy to Develop Creative Industry-Based Halal Tourism in Indonesia - Andi Fariana; Saripudin Saripudin; Ovalia Rukmana (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2022)
This study aims to propose a halal tourism model by adopting religious humanism integrated with the creative industry as a baseline. This is a legal study with a statutory approach, relying on various laws and regulations as the primary data, including MUI’s fatwas. This study found that religious humanism can be integrated into the development of the halal tourism industry based on creative industries, with Regional Regulations (Perda) as the guideline. The integration of religious humanism in development is possible with the participation of all stakeholders. This is because the development of halal tourism is not merely about tourism objects but also the community. In this case, religious people easily accept the idea and are willing to participate as long as the integration is structured.